THEORETICAL FEASIBILITY OF LEARNING MEDIA BASED ON ICT WITH CTL ON THE SUBJECT OF HUMAN RESPIRATORY SYSTEM - DWI YENI MUSDLALIFAH (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Based on the results of questionnaire spread, students have difficulty in understanding the biology concept because they feel that biology lesson needs too much memorizing, so that it is easy to be forgotten. As a consequence, it requires an approach that links the material to students real-world. One of the approach is CTL. Its implication can be facilitated by ICT-based learning media. One of the biology material being suitable to be taught using CTL is human respiratory system, because this material intimately associates with the daily life of students. This study aims to produce ICT media used to support learning with CTL, describe the theoretical feasibility of the media based on the result of experts and teacher reviews. The media was developed using the 4-D model. The theoretical feasibility was obtained from the review result of the media by experts and teacher. This research results an ICT media used to support learning with CTL. Based on review of the media, average scores of 3.87 to 4 are gained. It is categorized theoretically very feasible. The learning media based on ICT to support learning with CTL are feasible theoretically to be used in the learning process on the subject of human respiratory system. Keywords: learning media, CTL, the human respiratory sistem, class XI.